Associations between left atrial indices and cardiorespiratory and muscular fitness among physically active military personnel - Yen-Chen Lin; Yen-Chen Lin; Pang-Yen Liu; Kun-Zhe Tsai; Kun-Zhe Tsai; Kun-Zhe Tsai; Wei-Chun Huang; Wei-Chun Huang; Wen-Chung Yu; Wen-Chung Yu; Xuemei Sui; Carl J. Lavie; et al. (Frontiers in Cardiovascular Medicine)
BackgroundLeft atrial (LA) size and function are linked to exercise intolerance in heart failure, while associations between LA parameters and exercise performance remain unclear in athletes.ObjectivesThis study aimed to identify correlations between echocardiographic LA size, pressure, stiffness, and composite indices, and various exercise performance indicators.MethodsEchocardiographic parameters were obtained from 181 physically active military personnel receiving regular training and tests for a 3-km run and 2 min of push-ups and sit-ups. The top 16% of runners were compared sex-specifically, with the remaining 84% as controls to identify LA discriminators for running capacity. LA composite indices were defined as the LA volume index (LAVI) divided by the stiffness index (LASI) or pressure index (mitral E/e′). Spearman correlations were used to identify LA correlates with exercise performance. Generalized linear regressions were used to identify LA predictors of exercise performance with adjustments for potential covariates.ResultsThe top 16% of runners vs. controls had a lower LASI based on LA volume changes (LASI_v, 0.196 vs. 0.245, p = 0.013) and higher LAVI-to-LASI_v (12.30 vs. 8.08, p = 0.001) and LAVI-to-(mitral E/e′) (4.37 vs. 3.76, p = 0.038) ratios. The LAVI-to-LASI_v ratio was the most highly correlated shared LA parameter for running (|rho| = 0.403), push-up (rho = 0.335), and sit-up (rho = 0.352) performance. The LAVI-to-mitral E/e′ ratio was the most highly correlated, independent, and unique LA parameter for running (|rho| = 0.457) performance.ConclusionsThe LAVI-to-LASI_v ratio, comprising LA size and stiffness information, was the best correlate across exercise types, while the LAVI-to-mitral E/e′ ratio, comprising LA size and pressure information, was the best correlate of an endurance exercise, i.e., 3-km running performance.